Numerical investigation of influence of extent and position of a bypass on the performance of a single unit liquid desiccant based evaporative cooler / Raja Naveen Pamu, P. S. Kishore and Siva Subramanyam Mendu - Pamu, Raja Naveen; Kishore, P. S.; Mendu, Siva Subramanyam (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2024)
Air-conditioning of buildings is more energy-consuming with widely used vapour compression refrigeration systems in hot and humid areas. Alternatively, evaporative cooling does not show much effect in sultry regions because of increased humidity despite the minimum energy consumption. Indirect evaporative cooling is a promising alternative to direct evaporative cooling systems, but it suffers from low cooling effectiveness and is unsuitable for highly humid regions. Considering the above facts an alternative liquid desiccant-assisted modified M-cycle cooling system is proposed and examined numerically in the present work. The proposed cooling and dehumidification system is a simple unit incorporating chemical dehumidification and regenerative evaporative cooling in a single unit. A simultaneous heat and mass transfer model is developed for the numerical analysis. The numerical code is written in MATLAB and is validated with results available in the literature. Further, numerical analysis was carried out for the effect of various parameters on the performance of the proposed cooling system. The study shows an improvement of 19.2% in dew point effectiveness by incorporating an intermediate opening in the plate separating the product air and working air channels.